Management of Hridroga (CVD’S) - Manvitha Pagadala; Bikash Maharjan (International Journal of Ayurveda and Pharma Research, 2024)
Hridraya is an epitome of sustenance and co-ordination to maintain Ayu. It is considered as one of the three Marma sthana, and is the seat of Sarira, Buddhi, Indriya, Indriyartha, Saguna atma, Mana, etc so, any deviation in its functioning can be tremendously bereaving. Acharya Charaka, Sushruta, Vagbhata and Bhela have been unanimous regarding Hridaya being the seat of Manas and Buddhi. Hridroga is an ocean full of disease entities. In contemporary medical system, it is known as CVD i.e., Cardio-Vascular Disease. CVDs are the leading cause of death taking an estimated 17.9 million lives in 2019 accounting for whooping 32% of all the global deaths. Most cardiovascular diseases can be prevented by addressing behavioural risk factors such as tobacco use, unhealthy diet and obesity, physical inactivity and harmful use of alcohol. These risk factors can be effectively tackled by the judicious adherence to Dinacharya, Ratricharya, Ritucharya, Sadvritta niyamas, etc. Even in the state of disease, compliance with Sodhana procedures and Oushadhas can lead to alleviation of disease and qualitative improvement in the state of Ayu. This article gives 360° view of Shaman oushadhas related to Hridroga, which is explained by the Apta in various ancient texts.